Academician in the application of the history of Uzbekistan The place of the scientific heritage of V. V. Bartold. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article tells about the coverage of the history of Uzbekistan in the scientific heritage left by the famous orientalist, scholar of Central Asian history, author of many scientific works, Academician Vasily Vladimirovich Barthold.